2021
DOI: 10.1080/10717544.2021.1889717
|View full text |Cite
|
Sign up to set email alerts
|

Topical anesthetic and pain relief using penetration enhancer and transcriptional transactivator peptide multi-decorated nanostructured lipid carriers

Abstract: Many strategies have been developed to overcome the stratum corneum (SC) barrier, including functionalized nanostructures. Chemical penetration enhancers (CPEs) and cell-penetrating peptides (CPP) were applied to decorate nanostructured lipid carriers (NLC) for topical anesthetic and pain relief. A novel pyrenebutyrate (PB-PEG-DSPE) compound was synthesized by the amide action of the carboxylic acid group of PB with the amido groups of DSPE-PEG. PB-PEG-DSPE has a hydrophobic group, hydrophilic group, and lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The study concluded that the multi-decorated NLCs showed the most prominent anesthetic effect than single ligand decorated or undecorated LID NLC in vivo. Furthermore, this result was correlated with enhancement in skin penetration of lidocaine hydrochloride from multi-decorated NLCs (TAT/PB NLC) compared to the other formulae [57].…”
Section: Application Of Nlcs In Transdermal Drug Deliverymentioning
confidence: 81%
“…The study concluded that the multi-decorated NLCs showed the most prominent anesthetic effect than single ligand decorated or undecorated LID NLC in vivo. Furthermore, this result was correlated with enhancement in skin penetration of lidocaine hydrochloride from multi-decorated NLCs (TAT/PB NLC) compared to the other formulae [57].…”
Section: Application Of Nlcs In Transdermal Drug Deliverymentioning
confidence: 81%
“…CAL/TAN NS (200 mg) was dissolved in DMF (10 mL), EDC (20.0 mg) and NHS (12.0 mg) were added at 0 °C to activate the carboxylic acid groups of DSPE-PEG-COOH (A) (Jiang et al, 2021 ). Then MTP-131 (H-D-Arg-Dmt-Lys-Phe-NH 2 ) was dissolved in DMF (5 mL) and added dropwise to the above (A) and stirred for 24 h. The resulting solution was dialyzed (MWCO = 2 kDa) against distilled water for 24 h to get MTP-131 modified CAL/TAN NS (MTP-CAL/TAN NS).…”
Section: Methodsmentioning
confidence: 99%
“…A transmission electron microscope (JEOL, Tokyo, Japan) was used to visualize the surface morphology of ANP/TPP-BN-LPNs (Jiang et al., 2021 ). The particle size, polydispersity index (PDI), and zeta potential of LPNs were evaluated using dynamic light scattering (DLS) technique of NLC at room temperature on Malvern ZetaSizer Nano ZS90 (Malvern Instruments Ltd., Malvern, UK).…”
Section: Methodsmentioning
confidence: 99%